Two interesting new genera of Kalligrammatidae (Neuroptera) from the Middle Jurassic of Daohugou, China - Yang, Qiang; Makarkin, Vladimir N.; Ren, Dong (Zootaxa, 2011)
Two new genera and species of Kalligrammatidae (Neuroptera) Apochrysogramma rotundum gen. et sp. nov. and Protokalligramma bifasciatum gen. et sp. nov. are described from the Middle Jurassic of Daohugou, Inner Mongolia, China. The forewing of Protokalligramma gen. nov. is characterized by the generalised structure of MP, CuA, CuP and 1A, relatively scarce crossveins, absence of an eye-spot, and dense, long spinules (‘microtrichia’) occurring on its wing membrane. Apochrysogramma gen. nov. is the second genus in the subfamily Kallihemerobiinae, whose forewing easily differs from that of the type genus by the more rounded shape, much more numerous and closely spaced subcostal veinlets, branches of Rs and MP, less dense crossveins, and differently constructed eye-spot.